Mechanical and surface properties analysis of restorative materials submitted to erosive challenges in situ - Guedes, Ana Paula Albuquerque [UNESP]; Oliveira-Reis, Bruna [UNESP]; Catelan, Anderson; Suzuki, Thais Yumi Umeda; Briso, André Luiz Fraga [UNESP]; Santos, Paulo Henrique dos [UNESP] (Thieme, 2018)
Objective: This study aims to evaluate the effect of acidic solutions (AS) on surface roughness (Ra) and microhardness of restorative materials (RM). Materials and Methods: Eight volunteers wore intraoral palatal devices (IPD) containing samples of RM: Ketac Nano (KN); Ketac Nano + Biscover LV (KN-B); Esthet-X (EX); Esthet-X + Biscover LV (EX-B); Supreme XT (SXT); Supreme XT + Biscover LV (SXT-B); and bovine enamel. The samples were submitted to three phases: (1) immersion in 0.01M hydrochloric acid (HCl) - 10 min, three times/day (14 days); (2) immersion in soft drink (Sprite®) - 10 min, three times/day (14 days); and (3) keeping in saliva (14 days). Changes in Ra/microhardness were measured before/after the three phases. Statistical Analysis: ANOVA (α = 0.05) and Fisher's test. Results: Materials sealed with Biscover LV (B) presented lowest values in all periods. KN glass ionomer cement showed highest Ra values after exposure in AS. Application of B did not reduce the Ra for the composites studied, except for EX after immersion in HCl. AS promoted changes in Ra/microhardness of RM, except for sealed materials. Conclusions: The acids used were able to change the Ra and microhardness of RM, except of the sealed materials. The resin-modified GIC showed the most significant changes after immersion in AS; and the composites sealed with B, even after immersion in acidic solutions (AS), showed the lowest Ra values and the least degradation in microhardness, especially when subjected to low pH solutions.
Keywords: Carbonated drink; dental erosion; gastric juice; microhardness